Bercermin di kalbu rakyat - Hamengku Buwono X, Sultan of Yogyakarta, 1946- (Yogyakarta : Penerbit Kanisius, 1999)
Analysis on socio-economic, and political reformation in Indonesia; collected articles.
Keywords: Indonesia -- Politics and government -- 1998-; Indonesia -- Economic conditions -- 1945-1966.